A class of proximity-sensitive measures of relative deprivation - Oded Stark; Jakub Bielawski; Fryderyk Falniowski (University of Bonn, Center for Development Research (ZEF), 2017)
We introduce a new class of generalized measures of relative deprivation. The class takes the form of a power mean of order p . A characteristic of the class is that depending on the value of the proximity-sensitive parameter p , the class is capable of accommodating both a decreasing weight (the case of p > 1), and an increasing weight (the case of p (0,1) ) accorded to given changes in the incomes of the individuals who are wealthier than the reference individual, depending on their proximity in the income distribution to the reference individual.
Keywords: D31; D33; D63; H23; 330; Income distribution; Relative deprivation; Sensitivity to income transfers between wealthier individuals; Sensitivity to the proximity of changes in others' incomes